The effects of short-term power training on the starting technique of Korean elite female short-track speed skaters - Kwon, Y. H.
The purpose of this study was to evaluate the effects of a short-term power training on the selected biomechanical variables of the sprint start of the elite Korean female short-track speed skaters in an effort to identify the technical factors closely related to the leg power. Three Korean national skaters participated in this study as subjects. The power training was administered for two weeks (March 9 - 23, 1996) immediately after the 1996 World Individual Championships, but prior to the 1996 World Team Championships. This particular time frame was selected due to several reasons: (a) the skaters were expected to be highly motivated in this particular period of the season due to the World Individual Championships followed by the World Team Championships, (b) since the Team Championships had more weight on the short distance events (500 m and 1,000 m), the skaters needed a training specifically designed to enhance their start ability anyway, and (c) there was a possibility for the skaters to actually benefit from the training in preparation for the Team Championships. The power training was concentrated on the ankle joint due to several practical limitations. A Cybex-6000 was used in training. A pre-test was performed prior to the training and the training protocols were determined from the test results. Three-dimensional video motion analyses of the sprint starts of the subjects were performed before and after the training period to monitor the changes in the selected biomechanical variables such as the posture variables and the step variables. From the data analyses, it was concluded that: (a) the short-term power training improved the start ability of the subjects, (b) an early increase in the horizontal velocity was consistently observed among the skaters as a result of power training, (c) the start posture and the cadence and the step length in the first 2 steps of the start seemed to be the main biomechanical factors closely related to the leg power, and (d) therefore the technical drills in conjunction with the power training must be focused on lowering the start posture and increasing the cadence and the step length in first several steps.